Evaluasi Dampak Corporate Social Innovation Menggunakan Metode Qualitative Impact Assesment Protocol pada Kelompok Batik Seloka - Margono, Arbi Nur Syafi; Supriyanto, Akuat (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
This study evaluates the Batik Seloka Group Program's impact on the community using the Qualitative Impact Assessment Protocol (QUIP) method and identifies ways to strengthen the company's Social Innovation and Social Return on Investment (SROI) report for PROPER Emas. The main issues are high unemployment rates among the productive age group in Adipala Sub-district, the obstruction of batik sales due to Covid-19, and the need to improve batik skills. Using the QuIP approach, the impact of the Corporate Social Innovation program on the Batik Seloka group in Adipala Village, Cilacap Regency, was assessed. Eight semi-structured interviews and two Focus Group Discussions (FGDs) were conducted. Thematic analysis was used for data processing. Findings show a positive impact but highlight the need for improvements in environmental awareness and digitalization support. SROI and Social Innovation reports have potential bias and lack qualitative exploration. QuIP and SROI methods can complement each other, with SROI providing a framework for monetization and financial analysis, while QuIP offers a holistic approach to identify broader impacts. QuIP can reduce pro-project bias, providing a more accurate picture of program success in social innovation reports.